2012
DOI: 10.1128/jvi.00491-12
|View full text |Cite
|
Sign up to set email alerts
|

A Nonfucosylated Variant of the anti-HIV-1 Monoclonal Antibody b12 Has Enhanced FcγRIIIa-Mediated Antiviral Activity In Vitro but Does Not Improve Protection against Mucosal SHIV Challenge in Macaques

Abstract: Eliciting neutralizing antibodies is thought to be a key activity of a vaccine against human immunodeficiency virus (HIV). However, a number of studies have suggested that in addition to neutralization, interaction of IgG with Fc gamma receptors (Fc␥R) may play an important role in antibody-mediated protection. We have previously obtained evidence that the protective activity of the broadly neutralizing human IgG1 anti-HIV monoclonal antibody (MAb) b12 in macaques is diminished in the absence of Fc␥R binding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 50 publications
6
113
0
1
Order By: Relevance
“…Overall, the evidence suggests that eliminating Fc-mediated function impairs the protective antiviral activity of bNAbs, but it is unclear whether enhancing ADCC activity improves protective efficacy. A nonfucosylated variant of b12 that had enhanced viral inhibitory and killing abilities in vitro failed to improve protection efficacy in vivo relative to WT b12 (44). Thus, definitive evidence for ADCC remains elusive.…”
Section: Antibodies To Host Cell Receptorsmentioning
confidence: 99%
“…Overall, the evidence suggests that eliminating Fc-mediated function impairs the protective antiviral activity of bNAbs, but it is unclear whether enhancing ADCC activity improves protective efficacy. A nonfucosylated variant of b12 that had enhanced viral inhibitory and killing abilities in vitro failed to improve protection efficacy in vivo relative to WT b12 (44). Thus, definitive evidence for ADCC remains elusive.…”
Section: Antibodies To Host Cell Receptorsmentioning
confidence: 99%
“…The nonfucosylated variant of mAb b12 (NFb12), had increased FcγRIIIa binding and 10-fold improved potency in NKmediated ADCC and PBMC-mediated ADCVI assays, but, contrary to expectation, proved in vivo no more potent than wild-type Ab in protecting SHIV challenged rhesus macaques [127].…”
Section: The Influence Of Igg-fc Glycosylation On Fcγr-mediated Functionmentioning
confidence: 94%
“…Some of these glycoforms of Fc interact poorly with FcγRIIIa (e.g. fucosylated [120][121][122][123]) and so are possibly non-inflammatory versions of IgG that may be most appropriate for protection against mucosal challenge, especially considering the lack of evidence for improved protection in SHIV challenge studies by the non-fucosyl-variant of the b12 bNAb [127].…”
Section: The Influence Of Igg-fc Glycosylation On Fcγr-mediated Functionmentioning
confidence: 99%
“…133 In a follow-up study, using an afucosylated form of b12, which should drive enhanced ADCC, demonstrated limited improvement in antibody protective efficacy in a vaginal challenge model. 134 However, FccRIIIa + NK cells are necessary for ADCC, which are limited at mucosal barriers, 135 including the vaginal walls. This most likely resulted in the limited protection of these antibodies in vivo.…”
Section: Euler and Altermentioning
confidence: 99%